Presentation of Unearned Revenue Based on Government Accounting Standards (SAP) in the Financial Statements of the Land Office of North Tapanuli Regency for the Year 2024: PENYAJIAN NILAI PENDAPATAN DITERIMA DI MUKA BERDASARKAN SAP PADA LAPORAN KEUANGAN KANTOR PERTANAHAN KABUPATEN TAPANULI UTARA TAHUN 2024 - Sari, Selly Novita (Green Engineering Society, 2025)
Abstract. The value of advance revenue (PDDM) for land services at the North Tapanuli Regency Land Office still often has presentation issues. This creates the potential for misstatement of PDDM accounts in the 2024 Unaudited Balance Sheet. This study aims to ensure the accountability and presentation of ARR values in the 2024 Financial Statements of the Tapanuli Utara District Office of Land Affairs in compliance with the standards set forth in Government Regulation No. 71 of 2010. In conducting the research, the researcher employed a qualitative approach by interviewing informants and analyzing source documents. The sources interviewed were the Institutional Accounting Unit (SAI), Service Counter Officers, Technical Officers in the Field of Measurement and Mapping, and Technicians in the Field of Rights Determination and Registration. The researchers found that the presentation of advance income in the 2024 Unaudited Balance Sheet of the Tapanuli Utara District Land Office did not fully comply with generally accepted principles and regulations. Abstrak. Nilai Pendapatan Diterima di Muka (PDDM) atas layanan pertanahan pada Kantor Pertanahan Kabupaten Tapanuli Utara masih sering ditemukan permasalahan penyajian. Hal ini menimbulkan potensi salah saji akun PDDM pada Laporan Neraca Tahun 2024 Unaudited. Penelitian ini bertujuan untuk memastikan akuntabilitas dan penyajian nilai PDDM pada Laporan Keuangan Kantor Pertanahan Kabupaten Tapanuli Utara Tahun 2024 sesuai dengan standart yang ditetapkan PP Nomor 71 Tahun 2010. Dalam penelitiannya, Peneliti menggunakan pendekatan kualitatif dengan mewawancarai narasumber dan menganalisisis dokumen sumber. Yang menjadi narasumber adalah Unit Akuntansi Instansi (SAI), Petugas Loket Pelayanan, Petugas Teknis Bidang Pengukuran dan Pemetaan dan Petugas Teknis Penetapan dan Pendaftaran Hak. Hasil penelitian yang didapat oleh peneliti yaitu penyajian Nilai Pendapatan diterima di Muka pada Laporan Keuangan Kantor Pertanahan kabupaten Tapanuli Utara belum secara utuh mengikuti prinsip dan aturan yang berlaku umum.